(untitled) (Journal of Bio-Science, 2011)
Context: Female pheromone attracts the male eggplant shoot and fruit borer. The pheromone lure could be used in catching male adults to control this pest population in eggplant fields. Objectives: To study the efficacy of sex pheromone (lure) on the male moth catch of eggplant shoot and fruit borer (ESFB) Leucinodes orbonalis Guenée, shoot and fruit destruction and fruit yield in the control, IPM operated fields and farmer’s fields. Materials and Methods: For pheromone trap operation the experiments were done in four sites of the Rajshahi City. For IPM strategy two sites were selected in Paba upozilla. Pheromone traps were operated with the lure combination of 100:1 of E11-16: Ac and E11-16: OH. The trap consisted of a 3-liter capacity, 22-cm tall rectangular or round clear plastic container. A triangular hole is cut in any two opposite sides starting 3 to 4 cm from the bottom. The traps were randomly assigned in the study plots and installed with the help of bamboo stick. Sex pheromone trap height from ground level in the field was standardization for best trapping efficiency. For this traps were placed at 0.5 m and 1 m high above the ground in the field. In both cases control fields (without insecticide) of the same size were used in the experiments. Results: The number of ESFB males in ten trap catches were 1.7 to 4.5 with a mean number of 3.26 ± 0.32, 8.49 ± 0.36, 5.20 ± 0.24 and 14.95 ± 0.34 catch/trap in the Fields 1,2,3 and 4 respectively. The average moth catch per trap was 1.76 ± 0.56 and 4.54 ± 0.94 in the 0.5 and 1 m lure respectively. The damaged shoot was 19.34 ± 2.31% at 0.5 m lure height, whereas at 1m height no damaged shoot was recorded. A damaged fruit was recorded as 29.74 ±1.87% and 14.47 ± 2.29% with the fruit yield in q/ha was 176.58 ± 6.38% and 232.56 ± 6.63% at the 0.5 and 1m lure height plots respectively. When no trap was operated in the eggplant fields the shoot damage, fruit damage and fruit yield were 3.48%, 31.15% and 13.70 kg/100m2 respectively in the non-IPM blocks. On the otherhand they were 1.56%, 10.66% and 27.54 kg/100m2 in the IPM blocks respectively. Conclusion: The sex pheromones which have been extensively studied and already are in management programmes should be fine tuned to improve their efficacy in totality in an Integrated Pest Management Programme on the basis of feedback from the extension workers, and farmers. Key words: pheromone; Eggplant; Leucinodes orbonalis; IPM DOI: http://dx.doi.org/10.3329/jbs.v18i0.8768 JBS 2010; 18(0): 10-15